Diversifikasi Kuliner Mangrove Kelompok Usaha Berembang Asri Kecamatan Sungai Apit Kabupaten Siak - Prima Wahyu Titisari; Elfis Elfis; Syarifah Farradinna; Muhammad Akbar Maulana; Haliza Nurdilla; Putri Selaras (Asosiasi Dosen Akuntansi Indonesia, 2022)
The potential development of culinary diversity comes from various types of leaves and mangrove fruit. One coastal area with a potential mangrove area is Parit I/II, Sungai Apit District, Siak Regency. The purpose of this program was to the utilization of mangrove into processed culinary diversity as an effort to improve the economy through creative small industries that utilize the natural potential. Outcomes of this program were mangrove syrup, mangrove tea, mangrove chips, mangrove cake, mangrove nastar, dodol mangrove. Mangrove products were potentially to be developed in Sungai Apit and Siak Regency.